Squirrel cage induction motor fault diagnosis using lissajous curve of an auxiliary winding voltage: case of broken bars - Jelbaoui Yakout Khadouj; El Menzhi Lamiaà; Abdallah Saad (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
The detection of incipient faults has attracted industrials and researchers specific attention in order to prevent the motor breakdown, improve its reability and increase its lifetime. This paper presents a squirrel cage induction machine broken bar and rings diagnosis approach. This technic uses a new monitored signal as an auxiliary winding voltage related to a small coil inserted between two stator phases. Monitoring behaviors of the Lissajous curve of this auxiliary winding voltage park components under different load levels is the main key of this study. For this purpose, the squirrel cage induction machine modeling and the explicit expressions developed for the inserted winding voltage and its Park components will be presented. Then, an induction machine with different broken cases: one broken bar, two broken bars, broken end ring and broken bars with end ring are investigated. The simulation results confirm the validity of the proposed approach.